Social Equity in Urban Infrastructure Planning - . Sugiyantoro (The Institute for Research and Community Services, Institut Teknologi Bandung, 2001)
Social equity in urban infrastructure planning is important, especially where the infrastructure investment is high, and charging systems are applied: this will lead some people could not afford a fair delivery of services. The role of the planners is important to secure infrastructure delivery for the poor within the adopted and applied planning system in a respective country to anticipate the trend of privatization in production and delivery of infrastructure and services.